Big sky mountain ebook Book 2 of parable, montana series. - Miller, Linda Lael (Parable, Montana, 2012)
The "First Lady of the West," #1 New York Times bestselling author Linda Lael Miller, brings you to Parable, Montana—where love awaits. With his rugged good looks, vast wealth and family name, hell-raiser Hutch Carmody is still the golden boy of Parable, Montana. But he's done some growing up—making peace with his illegitimate half brother and inheriting half of Whisper Creek Ranch, which should have been all his. These days, Hutch knows there are some things money can't buy: like the heart of loving, ladylike divorcée Kendra Shepherd. Kendra's quiet mansion reminds her of what she wants most—a devoted husband and the pitter-patter of little feet. She can't get Hutch Carmody out of her mind. But a rough-and-tumble cowboy like Hutch, coming home for family dinner? Seems crazy! Then again, crazier dreams have become reality under the vast Montana sky.